Pemanfaatan E-Commerce dalam Pemasaran Hasil Pertanian di Kelurahan Teratai Kabupaten Batang Hari - Epit Erwandri; Sri Harimurti; Rusnani Rusnani; Enita Enita (Jurnal Abdimas ADPI Sains dan Teknologi, 2020)
In the current era of information technology, information technology has helped and facilitatedhuman life from various dimensions. One of the products of the very rapid development ofinformation technology is E-commerce. E-commerce is a means or place to buy and sell goods,services and information via the internet network on computers or other electronic means. Ecommerce(Electronic Commerce) can be used in marketing agricultural products and has had amajor influence on the growth of the social and economic order of society. The purpose of thisservice is so that farmers who are in the Teratai village of Batang Hari Regency can increase theirknowledge of marketing agricultural products through E-Commerce, and train participants tomarket their agricultural products through E-Commerce and provide real time price information.The method used is counseling and training activities. The results of this service activity are toprovide benefits for training participants in increasing their knowledge and skills for businessdevelopment through the use of marketing agricultural products using E-Commerce. By marketingproducts through E-Commerce, it is hoped that in the future the business carried out by them will bemore developed, and the sales volume of agricultural products will increase in a fast time.